Determinan Indeks Harga Saham Gabungan (IHSG) berdasarkan S&P 500, Harga Emas Dunia, dan Fed Rate pada Bursa Efek Indonesia Periode Tahun 2020 – 2024 - Aditya Yoga Arisandy; Jojok Dwiridotjahjono (Jurnal Simki Economic, 2026)
The capital market plays a crucial role in a country's economy, with the Jakarta Composite Index (JCI) being the primary indicator for assessing stock market performance in Indonesia. This study aims to analyze the influence of the S&P 500, global gold prices, and the Fed Rate on the JCI for the 2020–2024 period. A quantitative associative approach was used with multiple linear regression analysis techniques on 60 monthly data sets, including the S&P 500, global gold prices, and the Fed Rate as independent variables, and the JCI as the dependent variable. The results indicate that all three variables have a significant simultaneous effect, and partially prove that the S&P 500, global gold prices, and the Fed Rate each have a significant effect on the JCI movement. These findings confirm the strong integration of the domestic capital market with global dynamics and international monetary policy.